Visualization and comparative investigations of pulsating ferro-fluid heat pipe. (April 2017) - Gandomkar, A.; Saidi, M.H.; Shafii, M.B.; Vandadi, M.; Kalan, K.
Highlights: Nanofluid was unstable and also agglomerated and deposited in the copper pipe; whereas, it was stable in the Pyrex pipe. For the Pyrex heat pipe, applying the magnetic field caused weaker performance. For Pyrex PHP, increasing the concentration improved the performance. For the copper PHP, applying the magnetic field had the best performance. For copper PHP, concentration of the nanofluid in each case of the magnet and input power has an optimum value. Abstract: Pulsating heat pipes (PHPs) are among the best solutions for the electronics cooling due to their low cost, effectiveness and being passive. Experiments to study the effective factors on heat transfer performance have been designed and as a result, improvement of ferrofluid PHP performance has been achieved. Two different heat pipes made of copper and glass were prepared to investigate the behavior of magnetic nanofluids. In order to find the best condition for heat transfer performance, different concentrations of nanofluid with a filling ratio of 50% were tested in 3 different cases of magnetic field. The results indicated that the ferrofluid is more stable in the glass PHP. It also shows that the presence of magnetic field in the copper PHP has the best outcome while in the glass PHP, the absence of magnetic field results better. It was detected that using a more concentrated ferrofluid causes a better performance in the copper PHP only when the magnetic field is applied, while in the glass PHP, increasing the concentration of ferrofluid improves the performance of the PHP in all conditions of applying the magnetic field.